The Multifaceted Roles of B Cells in the Thymus: From Immune Tolerance to Autoimmunity - Castañeda, Justine; Hidalgo, Yessia; Sauma, Daniela; Rosemblatt, Mario; Bono, María Rosa; Núñez, Sarah (Frontiers in Immunology, 2021)
The thymus is home to a significant number of resident B cells which possess several unique characteristics regarding their origin, phenotype and function. Evidence shows that they originate both from precursors that mature intrathymically as well as the entry of recirculating mature B cells. Under steady-state conditions they exhibit hallmark signatures of activated B cells, undergo immunoglobulin class-switch, and express the Aire transcription factor. These features are imprinted within the thymus and enable B cells to act as specialized antigen-presenting cells in the thymic medulla that contribute negative selection of self-reactive T cells. Though, most studies have focused on B cells located in the medulla, a second contingent of B cells is also present in non-epithelial perivascular spaces of the thymus. This latter group of B cells, which includes memory B cells and plasma cells, is not readily detected in the thymus of infants or young mice but gradually accumulates during normal aging. Remarkably, in many autoimmune diseases the thymus suffers drastic structural atrophy and infiltration of B cells in the perivascular spaces, which organize into follicles similar to those normally found in secondary lymphoid organs. In this review we provide an overview of the pathways involved in thymic B cell origin and present an integrated view of both thymic medullary and perivascular B cells and their respective physiological and pathological roles in central tolerance and autoimmune diseases.